أثر تقدير الذات و علاقته بالتحصيل الدراسي لدى المراهق المتفوق - عسنون, حكيمة (كلية العلوم الإجتماعية لجامعة مستغانم, 2024)
هدفت هذه الدراسة إلى معرفة مستوى تقدير الذات لدى المراهق المتفوق ومحاولة الإجابة على التساؤل التالي: "كيف يؤثر تقدير الذات لدى المراهق المتفوق على تحصيله الدراسي.؟". كما تم الإعتماد على المنهج العيادي بإستخدام تقنية دراسة الحالة، ولأختبار صحة الفرضية إستخدمنا الأدوات التالية: المقابلة نصف موجهة ،الملاحظة المباشرة، ومقياس تقدير الذات لكوبر سميث، و قد طبقت الدراسة على عينة مكونة من حالتين مراهقين. متفوقين في الدراسة (ذكر و أنثى) تم اختيارهما بطريقة قصدية والذين تتوفر فيهما جملة من الخصائص التي تم تحديدها من قبل الباحثة، أصفرت النتائج على ما يلي : إذا إنخفض مستوى تقدير الذات لدى المراهق المتفوق ينخفض تحصيله الدراسي، من أهم دوافع تقدير الذات شعوره بالتميز، التقدم و الرفعة، تكمن علاقة تقدير الذات لدى المراهق بتحصيله الدراسي أنها أساس التفوق، التقدم و التحصيل الجيد.
دراسة عيادية لحالتين بولاية مستغانم
This study aimed to determine the level of self-esteem of the outstanding adolescent and attempt to answer the following question: “How does the self-esteem of the outstanding adolescent affect his academic achievement?”. The clinical approach was also relied upon using the case study technique, and to test the validity of the hypothesis we used the following tools: semi-directed interview, direct observation, and the Cooper-Smith self-esteem scale. The study was applied to a sample of two adolescent cases, excelling in their school careers (male and female) that were chosen intentionally and have a set of characteristics that were identified by the researcher, The results were as follows: If the level of self-esteem of an outstanding adolescent decreases, his or her academic achievement decreases ; one of the most important drivers of self-esteem is a feeling of distinction, progress and élévation ; the relationship between the adolescent’s self-esteem and his académic achievement is that it is the basis for excellence, progress and good achievement.
Keywords: تقدير الذات، التحصيل المدرسي، المراهق، التفوق الدراسي.; self - esteem - school achievement - adolescents - academic excellence.